Estado nutricional ao diagnóstico oncológico como possível marcador do excesso de peso em crianças e adolescentes sobreviventes do câncer - Teixeira, Julia Ferrari Carneiro [UNIFESP] (2016)
Obesity is a late effect recognized in survivors of childhood cancer, but news studies have shown that the most recent survivors, no different from population estimates and suggest that external factors, as well as the genetic characteristics of the individual, may have greater influence on gain weight among the survivors. Within this reality, the question is about the quantity and quality of food from this group and its possible correlation with obesity. Moreover, the limitation of studies with survivors in developing countries and reduced work with measured data justifies this work. Thus, we had as objective to evaluate the previous and current nutritional status and food intake and antineoplastic treatment and their relationship with obesity in childhood cancer survivors. All patients treated at a referral center and attended the clinic of late effects, which survived for at least 2 years after treatment, they were eligible for inclusion. Anthropometric data and information on the antineoplastic treatment were collected. For analysis of nutritional status, as well as for the food characteristics, we divided the patients into two groups, group 1 consisting of leukemia survivors and CNS, grouped due to similar treatment and group 2, consisting of the remaining survivors. The main finding of our study was the correlation of BMI at diagnosis with excess weight after treatment in both groups was not observed correlation with the anticancer treatment. Moreover, we observed changes in body composition, characterized by lean body mass reduction. The feeding of these patients, regardless of cancer diagnosis, is unbalanced, especially the high protein intake and saturated fatty acids, as well as reduced suitability of vitamins and minerals. The treatment helps to change body composition and diseases associated with excess tissue. However, it is believed that current lifestyle associated with individual characteristics, contributes substantially to the development of metabolic complications in survivors. Early identification of risk groups is essential to minimize the adverse effects of antineoplastic therapy and promotion of healthy eating habits.